Hirtle Callaghan & Co - Elias, Jaan; Quinn, James, active 2020; Blumenthal, Adam (London : Yale School of Management, 2020)
In August 2019, Stephen Vaccaro, Yale MBA '03, became the director of private equity at Hirtle, Callaghan & Co., LLC (HC), a leading investment management firm associated with pioneering the outsourced chief investment office (OCIO) model for college endowments, foundations, and wealthy families. Vaccaro, who would work under the guidance of Deputy CIO Dan McCollum (Columbia MBA '03), was tasked with spearheading efforts to grow HC's private equity (PE) market value from $1 billion to a new target of roughly $3 billion in order to contribute to the effort of generating higher long-term returns for clients. These new allocations, approved recently by HC's senior team, represented a sizable shift in HC's commitment to PE-from roughly 6% to 18% of the firm's more than $17 billion in assets under management (AUM).
Originally Published InElias, J., Quinn, J., & Blumenthal, A. (2020). Hirtle Callaghan & Co. 20-028. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Investment advisors -- Case studies; Investments -- Case studies; Stockbrokers -- Case studies